Antibiotic prophylaxis and its effect on postprocedural adverse events in endoscopic retrograde cholangiopancreatography for primary sclerosing cholangitis. Issue 1 (5th December 2022) - Gustafsson, Arvid; Enochsson, Lars; Tingstedt, Bobby; Olsson, Greger
Abstract: Background and Aim: Primary sclerosing cholangitis (PSC) is characterized by multiple strictures of the biliary tree. Patients with PSC frequently require repeated endoscopic retrograde cholangiopancreatography (ERCP) procedures. These procedures are encumbered by an increased incidence of infectious adverse events such as cholangitis. Evidence regarding whether antibiotic prophylaxis (AP) should be administered is sparse; however, prophylaxis is recommended. We aimed to determine whether AP affects the rate of postprocedural infectious and overall adverse events. Methods: We conducted a retrospective cohort study and extracted all ERCP procedures with indicated PSC performed between 1 January 2006 and 31 December 2019, which were registered in the Swedish Registry for Gallstone Surgery and ERCP (GallRiks). The exclusion criteria were incomplete 30‐day follow‐up, non‐index procedures, or ongoing antibiotics. The main outcomes were postprocedural infectious adverse events and overall adverse events at the 30‐day follow‐up. Results: A total of 2144 procedures with indication of PSC were eligible for inclusion. AP was administered in 1407 (66%) of these procedures. Patients receiving AP were slightly younger (44 vs 46 years, P  = 0.005) and had more comorbidities (ASA ≥3, 19.8% vs 13.6%; P   < 0.001). Procedures with AP demonstrated an infectious adverse event rate of 3.3% compared to 4.5% for non‐AP procedures ( P  = 0.19). Postprocedural infectious adverse events (odds ratio [OR] 0.76, 95% confidence interval [CI] 0.48–1.21) and overall adverse events (OR 0.79, 95% CI 0.60–1.04) did not differ between AP and non‐AP. Conclusion: Patients with PSC who undergo ERCP have the same frequency of adverse events regardless of whether AP was used. Abstract : Patients with primary sclerosing cholangitis are encumbered with increased incidence of infectious adverse events when undergoing endoscopic retrograde cholangiopancreatography procedures. In this retrospective cohort study, we investigated the use of antibiotic prophylaxis in 2144 such procedures. We found no reduction in adverse events even if prophylaxis was administered.